Proses Penanganan Anak Pengguna Narkotika Di Bawah Usia 12 Tahun - Sinaga, Aline Philia Antana; Sahetapy, Elfina Lebrine (Fakultas Hukum Universitas Surabaya, 2023)
Drug abuse is currently threatening minors. This situation will have a impact on the future of the child and also the future life of the country. Lack of control over narcotics causes children under the age of 12 years to be threatened. Children are not understand the existing environment and situation. Minors as narcotics addicts will receive treatment and be differentiated in their settlement efforts because children are still unable to enter into the existing legal process. The research method used empirical juridical research methods. Using empirical facts from individual behavior in the form of verbal behavior taken through interviews and direct observations. As a state of law, must implement a legal system so that the handling of children as narcotics users will still receive handling efforts for the completion of existing cases and children will still get the rights as they should be by the nature of a child.